Experimental Study on the Vibration of an Overhung Rotor with a Propagating Transverse Crack - S.A. Adewusi; B.O. Al-Bedoor (Shock and Vibration)
This paper presents an experimental study on the dynamic response of an overhung rotor with a propagating transverse crack. The effects of a propagating transverse crack and side load on the dynamic response of an overhung rotor are investigated in order to identify vibration signatures of a propagating crack in rotating shafts. Startup and steady state vibration signatures were analyzed and presented in the form of Bode plots, Frequency Spectrum Cascades, Frequency Spectrum Waterfalls and orbits. The startup results showed that crack reduces the critical speed and increases the vibration amplitude of the rotor system. It also excites 2X vibration in the startup vibration signatures. The steady state results showed that the propagating crack produces changes in vibration amplitudes of 1X and 2X vibration harmonics and excites 3X harmonic just before fracture. During crack propagation, 1X amplitude may increase or decrease depending on the location of the crack and the direction of vibration measurement while 2X amplitude always increases. The steady state vibration signal of a propagating crack also produces a two-loop orbit.